The Relationship of Exclusive Breastfeeding to Stunting in Toddlers in Jambangan District, Surabaya, Indonesia - Ganis Sasmita Kusumahati; Novera Herdiani (Community Medicine and Education Journal, 2023)
Stunting is a condition of failure to thrive in children, which is characterized by a height that does not match their age due to chronic malnutrition, especially in the first 1000 days of life, that is, from the mother's womb until the age of the toddler is 2 years. East Java is one of the regions with a prevalence of quite high stunting. This study aimed to determine the relationship between exclusive breastfeeding and stunting in toddlers in the Jambangan District, Surabaya. This study was a cross-sectional descriptive observational study and used secondary data from the Kebonsari Health Center in Surabaya, where as many as 3906 toddlers were included in this study. Data analysis was carried out using SPSS univariate and bivariate. The results of the study showed that of the 3906 toddlers who became the research sample, 0.26% of them were stunted. In conclusion, there is no relationship between exclusive breastfeeding and stunting (p>0.05).